Goodbye Marcus Welby: The Professional Entry of Primary Care Physicians - Patricia M. Thompson (Adult Education Research Conference, 2008)
In this paper I report the findings of a study of primary care physicians’ experiences as they enter the medical profession after residency training. Using narrative inquiry to learn about the participants’ experiences, this study found that despite strong professional socialization during training, the participants constructed their medical practices to meet both their professional and personal aspirations while conforming to organizational expectations.